Troxerutin Induces Anticancer Efficacy in Human Hepatoblastoma Cell Line through G0/G1 Arrest and Mitochondria-Mediated Apoptosis - Nalini Namasivayam, Dr (International Journal of Pharmaceutical & Biological Archive, 2016)
Hepatoblastoma (HB) is the third most common abdominal neoplasm that occurs in children among the age group of 6 months-3 years. The present study was aimed to explore the anticancer efficacy of troxerutin (TX) on human colon hepatoblastoma cell line Hep G2. The cells were treated with different concentrations of TX (0.19-100 Î¼M) to evaluate the effective IC50 dose at different time point 24 h, 48 h and 72 h. The effects of troxerutin on apoptotic morphology, mitochondrial membrane potential and on reactive oxygen species generation were examined by specific staining techniques in a time dependent manner (24 h and 48 h). The effect of TX on oxidative stress markers was determined by biochemical evaluation of antioxidants and lipid peroxidation profile and effect on DNA damage was determined by comet assay. Our results revealed that treatment with TX induced morphological changes and apoptotic characteristics including chromatin condensation, nuclear and DNA fragmentation in Hep G2 cells. Furthermore, our results revealed that treatment with TX induced mitochondrial membrane depolarization and significant (p<0.05) alterations in the oxidative stress markers (TBARS, SOD, CAT, GPx and GSH) as compared to the control untreated cells. Our findings conclude that TX significantly suppressed the cell viability and induced apoptosis in the Hep G2 cells in a dose and time dependent manner.